Modtagelsessamspillets lokale økologi: Identitet og mening til forhandling - Revsbæk, Line (Academic Quarter | Akademisk kvarter, 2013)
Based on an empirical study of organizational entry and employee induction in a Danish private sector company, and supported by complexity theory perspectives, the article develops the notion of ‘organizational temporality’ of relevance when researching and practicing employee induction. Organizational life is understood as evolving complex responsive processes of local interaction forming and being formed by global patterns of interaction (Stacey 2010, Prigogine 1997). It is argued that formalized induction practices based on assumptions of newcomer as ‘unknowledgeable’ and oldtimer as ‘knowledgeable’ is in possible discord with actual learning processes and related feelings of uncertainty experienced by newcomers and oldtimers in rapidly changing organizations. To reduce costly newcomer turnover many organizations put much energy into optimizing formalized global induction programs. This article contends that organizational entry, socialization and newcomer–oldtimer interactions are best understood in a local micro-organizational perspective. Based on this contention the term ‘ecology of entry’ is developed.